Analisis Kebutuhan Pelayanan Komplementer di PMB Wilayah Surabaya - Nur Hidayatul Ainiyah (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: Currently, midwives have implemented complementary and alternative medicine in the practice of midwifery services. Midwives argue that complementary therapies can help reduce medical interventions and as a means to empower women. This is consistent with the principles of midwifery, which state that childbirth is a natural process and there is a role for the midwife in facilitating support and options for women. This condition is a separate phenomenon for further research. The purpose of this study is to analyse the need for complementary services in PMB Surabaya.Methods: The research used the survey method through the preparation stage, data collection, processing, and analysis of the results. The research subjects are community and midwives who practice complementary midwifery services. Samples were taken through a purposive sampling technique. Quantity data in the frequency distribution table and cauldron data are presented in an interactive model. Data is analysed and presented quantitatively in the form of a frequency distribution.Results: The study’s results explain that most of the respondents are 36-45 years old (53.3%), have the latest education in DIII Midwifery, 11-20 years of practice (46.7%), and most of them have attended seminars/training on services complementary obstetrics.Conclusion: The analysis of the need for complementary services in the Independent Midwife Practice (PMB) in Surabaya was done mainly by massage therapy, with as many as seven midwives (46.7%). Massages performed by midwives include baby massage, breast massage, and oxytocin massage. Other complementary therapies are yoga (26.7%), hypnotherapy (20.0%), and herbal medicine (6.7%).